Atrial septal aneurysm: Prevalence and covariates in adults. (15th November 2016) - Yetkin, Ertan; Atalay, Hakan; Ileri, Mehmet
Abstract: Background: Atrial septal aneurysm is a localized deformity of interatrial septum, generally at the level of fossa ovalis which protrudes into right or left atrium or both. The purpose of this study was to assess the frequency and covariates of atrial septal aneurysm in adult patients undergoing transthoracic echocardiography in our outpatient clinic. Materials and methods: From December 2011 to May 2016, 16, 570 patients were included in the study. Records of patients were retrospectively analyzed from our previously established database. All cardiovascular examinations and echocardiographical examinations had been done during this period. Briefly, protrusion of interatrial septum more than 15 mm into the right or left atrium with an at least 15 mm diameter base of interatrial septum confirmed the diagnosis of atrial septal aneurysm. Results: Atrial septal aneurysm has been documented in 393 patients (2.4%) in our study population. Mild to moderate mitral and aortic valve regurgitation have been demonstrated in 153 (39%) patients and in 61(16%) patients respectively. Sixty one (16%) of patients had the diagnosis of supraventricular arrhythmia of whom 52% underwent radiofrequency ablation procedure. Conclusion: In conclusion we have documented that valvular regurgitation and supraventricular arrhythmias are common concurrent pathologies with atrial septal aneurysm.